Nanoencapsulation enhances the post-emergence herbicidal activity of atrazine against mustard plants - Oliveira, Halley Caixeta; Stolf-Moreira, Renata; Martinez, Cláudia Bueno Reis; Grillo, Renato [UNESP]; Jesus, Marcelo Bispo de; Fraceto, Leonardo Fernandes [UNESP] (Public Library Science, 2015)
Poly(epsilon-caprolactone) (PCL) nanocapsules have been recently developed as a modified release system for atrazine, an herbicide that can have harmful effects in the environment. Here, the post-emergence herbicidal activity of PCL nanocapsules containing atrazine was evaluated using mustard (Brassica juncea) as target plant species model. Characterization of atrazine-loaded PCL nanocapsules by nanoparticle tracking analysis indicated a concentration of 7.5 x 10(12) particles mL(-1) and an average size distribution of 240.7 nm. The treatment of mustard plants with nanocapsules carrying atrazine at 1 mg mL(-1) resulted in a decrease of net photosynthesis and PSII maximum quantum yield, and an increase of leaf lipid peroxidation, leading to shoot growth inhibition and the development of severe symptoms. Time course analysis until 72 h after treatments showed that nanoencapsulation of atrazine enhanced the herbicidal activity in comparison with a commercial atrazine formulation. In contrast to the commercial formulation, ten-fold dilution of the atrazine-containing nanocapsules did not compromise the herbicidal activity. No effects were observed when plants were treated with nanocapsules without herbicide compared to control leaves sprayed with water. Overall, these results demonstrated that atrazine-containing PCL nanocapsules provide very effective post-emergence herbicidal activity. More importantly, the use of nanoencapsulated atrazine enables the application of lower dosages of the herbicide, without any loss of efficiency, which could provide environmental benefits.